Occurrence and distribution of alternaria species in seeds of rapeseed mustard in Nepal - Srestha, S.K.; Munk, L.; Mathur, S.B. (Copenhagen (Dinamarca), 1998)
Sumario (En)
17 ref.
Keywords: BRAáICA NIGRA; ALTERNARIA BRAáICAE; ENFERMEDADES INFECCIOSAS; SEMILLAS; NEPAL